Customising an instrumented footrest to measure lower-body push forces in competitive kayaking - Ho, Benjamin Guan Meng (2018)
Traditional research on sprint kayaking have mainly focused on the relationship between paddle force and boat speed as a performance indicator. Much less is known about the effect of leg drive during paddling on boat speed. It is important to be able to quantify the forces applied on the footrest of the kayak and observe how it changes during paddling to obtain a holistic view of the technical ability of a kayaker, This project focused on the design and development of an instrument that is capable of measuring the amount of force a kayaker applies on the footrest of a kayak ergometer; an equipment that kayakers often train on when training on land. A prototype was produced and tested to determine its performance characteristics based on a standard set of performance criteria for sensor devices. Thereafter, the instrument was optimised for functional use. This report first presents a brief review of the biomechanics of kayaking and prior research related to the subject and this project, followed by a literature review that set the foundation for the creation of the initial design of the instrumentation. Thereafter, the report documents a series of loading tests conducted to determine the performance characteristics of the designed instrumentation. Human trial tests were also conducted to determine its practicality in kayaking performance research. Feedback was then received from the trial tests from which allowed us to further modify the instrumentation hardware and software for functional use. Finally, the report ends with concluding statements that highlight possible future developments to be made.